2002
DOI: 10.1164/ajrccm.165.4.2108006
|View full text |Cite
|
Sign up to set email alerts
|

Improved Arterial Oxygenation with Biologically Variable or Fractal Ventilation Using Low Tidal Volumes in a Porcine Model of Acute Respiratory Distress Syndrome

Abstract: We compared biologically variable ventilation (V (bv); n = 9) with control mode ventilation (V (c); n = 8) at low tidal volume (VT)--initial 6 ml/kg--in a porcine model of acute respiratory distress syndrome (ARDS). Hemodynamics, respiratory gases, airway pressures, and VT data were measured. Static P-V curves were generated at 5 h. Interleukin (IL)-8 and IL-10 were measured in serum and tracheal aspirate. By 5 h, higher Pa(O(2)) (173 +/- 30 mm Hg versus 119 +/- 23 mm Hg; mean +/- SD; p < 0.0001 group x time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 29 publications
8
69
3
2
Order By: Relevance
“…5 In animal models of ARDS, variable ventilation strategies are superior to conventional control mode mechanical ventilation (CMV) or CMV with recruitment maneuvers with respect to lung mechanics, gas exchange, surfactant content, and inflammatory mediators with an overall decrease in distending stress. [5][6][7][8][9][10][11][12] In a recent computed tomography (CT) imaging study, we confirmed BVV induced recruitment of both poorly and non-aerated lung regions. 13 In this study, we hypothesized that the recruitment benefit and periodic low V T breaths seen with BVV could result in enhanced resolution of edema fluid in ARDS.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…5 In animal models of ARDS, variable ventilation strategies are superior to conventional control mode mechanical ventilation (CMV) or CMV with recruitment maneuvers with respect to lung mechanics, gas exchange, surfactant content, and inflammatory mediators with an overall decrease in distending stress. [5][6][7][8][9][10][11][12] In a recent computed tomography (CT) imaging study, we confirmed BVV induced recruitment of both poorly and non-aerated lung regions. 13 In this study, we hypothesized that the recruitment benefit and periodic low V T breaths seen with BVV could result in enhanced resolution of edema fluid in ARDS.…”
supporting
confidence: 76%
“…These parameters were chosen as multiple previous studies have demonstrated significant BVV advantages with respect to lung mechanics, gas exchange, and inflammatory mediators within this time period with a similar number of subjects, 6,7 and Ware and Matthay 1 were able to demonstrate significant differences in fluid clearance rates in clinical subjects over a similar time frame. Given the more modest effects seen with a less severe injury model, however, significant differences were limited to the CT findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the benefits in gas exchange, the most striking and common finding during variable controlled mechanical ventilation across different studies is the improvement in lung mechanics. In an experimental model of the acute respiratory distress syndrome (ARDS), variable controlled mechanical ventilation improved lung function compared to the ARDS Network lung protective strategy, as well as the open lung approach [14,15]. In addition, it has been shown that variable ventilation may also be used during assisted ventilation by means of random variation of pressure support (variable pressure-support ventilation [PSV]) leading to comparable improvements in lung function compared to conventional PSV [16].…”
Section: Modes Of Variable Ventilationmentioning
confidence: 99%